Comparative Analysis of Students' Reading Ability Based on KWL, CIRC, and DRA Learning Models and Reading Interest - Somadayo, Samsu; Pamuti, Pamuti; Wahjuningsih, Eka; Husain, Siti Rohayati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
Reading activity is an important learning skill for students to master. This research aims to determine the differences in reading comprehension abilities between students who take part in learning using the KWL model, CIRC model, and DRA model; differences in reading comprehension abilities between students who have high, medium, and low interest in reading;[HA1] and describe the results of the interaction of learning models and interest in reading on comprehension abilities. This quantitative research uses experimental methods. Data collection techniques using test and non-test techniques. Test techniques are used to measure reading comprehension ability, while non-test techniques are used to collect reading interest data. The analysis technique used in this research uses two-way ANOVA with the help of SPSS 25. The results of the research data analysis show no real difference in the reading comprehension ability of students who use the KWL and CIRC learning models. Still, it significantly differs from students using the DRA learning model. It can also be seen that students with low and moderate interest in reading are not significantly different, while students with high interest in reading are significantly different.